Acceptability of co-living space as new type of accommodation in Davao City a study based on user preference and perception - Puig, Pamela B. (2021)
Co-living as an emerging accommodation alternative, seeks to create community and provide sustainable development through applying the sharing economy model into living space. It is bridging the housing gap that is not supported by other traditional typologies of housing design. Co-living has large market potential in the Philippines, particularly in Davao City, wherein the rapid economic expansion and population growth are expected to boost the real estate sector. But then again, the opportunities for co-living to thrive varies across cities, depending on various factors. There is a lack of understanding of the realities of these spaces which limits the potential of the co-living model. Given that there are not many comprehensive studies of co-living in the local context, this is where the main problem arises. The researcher determined how acceptable co-living is as a new type of accommodation based on the perception and preference of renters of shared accommodations and homeowners in Davao City, and co-living residents. The research design is a descriptive study with both quantitative and qualitative data. Actual surveys were conducted to renters of shared accommodations from (1) Talomo (2) Poblacion (3) Buhangin (4) Agdao, and (5) Panacan. Homeowners in Davao City and co-living residents were requested to answer the online survey. The respondents were asked about their perceptions and preferences on the attributes under the different product levels of co-living. The results were subjected to statistical analysis and content analysis, respectively. The result of the study revealed that all core benefits, augmented products, and actual products are generally acceptable for the consumers. The majority of the renters and homeowners are willing to pay to stay in a co-living space. The experience and perceptions of co-living residents also solidify the advantage of co-living spaces over traditional shared accommodations. Therefore, co-living is acceptable as a new type of accommodation in Davao City. However, based on their opinions, there are still changes to be done to improve the co-living model. To experience the full ecological, social, and economic benefits of co-living, it is necessary to have an in-depth understanding of consumers' perceptions and preferences for good market efficiency and better-fitting dwellings.